2018
DOI: 10.1088/1361-6528/aaaacd
|View full text |Cite
|
Sign up to set email alerts
|

Titanium contacts to graphene: process-induced variability in electronic and thermal transport

Abstract: Contact resistance (R ) is a major limiting factor in the performance of graphene devices. R is sensitive to the quality of the interface and the composition of the contact, which are affected by the graphene transfer process and contact deposition conditions. In this work, a linear correlation is observed between the composition of Ti contacts, characterized by x-ray photoelectron spectroscopy, and the Ti/graphene contact resistance measured by the transfer length method. We find that contact composition is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…However, it should be noted that the interfacial chemistry between the graphene and the substrate can significantly influence the heat transfer across these interfaces as mentioned in the preceding Section . Furthermore, Freedy et al have shown that the h K across Ti/Gr/SiO 2 contacts that are mostly studied in literature, largely depends on the oxide composition at the contact. By varying the base pressure and the deposition rate of the encapsulating Ti layers, they show that the oxide composition in the Ti layer can be systematically changed.…”
Section: Thermal Boundary Conductance Across Interfaces Composed Of 2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that the interfacial chemistry between the graphene and the substrate can significantly influence the heat transfer across these interfaces as mentioned in the preceding Section . Furthermore, Freedy et al have shown that the h K across Ti/Gr/SiO 2 contacts that are mostly studied in literature, largely depends on the oxide composition at the contact. By varying the base pressure and the deposition rate of the encapsulating Ti layers, they show that the oxide composition in the Ti layer can be systematically changed.…”
Section: Thermal Boundary Conductance Across Interfaces Composed Of 2mentioning
confidence: 99%
“…For Au/Ti/Gr/SiO 2 without any surface functionalization, an intrinsic h K ≈33 MW m −2 K −1 has been measured that is four times smaller than that of the Au/Ti/SiO 2 interface . Recent studies have also shown that h K measured across Au/Ti/Gr/SiO 2 and Au/TiO x /substrate interfaces are not only impacted by the weak interfacial bonding, but are also significantly impacted by the oxide compositions at the Ti contacts that are highly dependent on the Ti deposition rate and base pressure …”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
“…37,38 The influence of Ti adhesion layers has also been examined for its effects on thermal transport in thin gold films on various substrates. 26,39,40 As interfaces can become the dominant resistors in thin film systems, their thermal management is paramount in multilayer geometries, and thus, understanding the growth and chemistry mechanisms that influence the thermal performance of these adhesion layers is of the utmost importance.…”
mentioning
confidence: 99%
“…Lince et al [28] drew attention to this fact and speculated that their own evaporation of Ti may have resulted in some Ti oxidation because their depositions were carried out at 3 × 10 −8 Torr, while McGovern et al [16] used 2 × 10 −9 Torr. This may seem insignificant, however, McDonnell et al [16] would later show large differences in Ti depositions carried out under~10 −9 Torr and~10 −7 Torr conditions, while Freedy et al [73] would show that even 10 −6 Torr to 10 −7 Torr could yield large changes in the Ti chemistry.…”
Section: Interface Chemistrymentioning
confidence: 96%
“…XPS was used to verify that Ti deposition in HV can be completed oxidized (inset of Figure 4a). More recent work by Freedy et al [73] further tested this hypothesis by examining the Ti chemistry as a function of vacuum pressure and deposition rate in HV. These result (shown in Figure 4c) showed that the Ti metal to Ti oxide ratio could be readily altered by varying either vacuum pressure or Ti deposition rate, which is consistent with the model proposed by McDonnell et al [18].…”
Section: Deposition Ambientmentioning
confidence: 99%